x^2 = the first integer
(x - 1)^2 = the second integer.
x^2 - (x - 1)^2 = ?
First, let's plug a number into our equation for x.
(2)^2 - (2 - 1)^2 = ?
4 - (1)^2 = ?
4 - 1 = 3
As we can see the difference is odd but it's also the sum of the two consecutive integers.
2 + 1 = 3.
This works for all numbers. Let's plug another number into our equation for x.
(4)^2 - (4 - 1)^2 = ?
16 - (3)^2 = ?
16 - 9 = 7
4 + 3 = 7
Try any number and it will always be odd.
A. you would put in 7 for X and 3 for Y.
3 + 7 = 10
2(10) = 20
Replace x with x+3:
f(x+3) = (x+3)²
which is x² translated 3 units left
Sheila is incorrect! I think what she did is think the 38 was actually a 35, which WOULD of made her statement true, but since it's 38, she's very incorrect. Sheila should be using the quotient for the size of each piece. 38 divided by 5 is 7.6. The correct answer is 7.6 inches.